The importance of the Brasilia Rules for effective access to justice in family matters in Mexico - García Sánchez, Arán (2021)
This research seeks to establish the implications of the Brasilia Rules in Mexico, based on the study of the criteria contemplated in these rules, the conceptual delimitation of the right of access to justice, and the establishment of its implications in the area of family justice. In this sense, a rigorous study was carried out on the importance and validity of the application of the Brasilia Rules in judicial proceedings in family matters in Mexico, with the intention of making effective the right of access to justice in favor of the members of the families that are in a situation of vulnerability at the moment of facing the justice systems.